Efficacy and safety of adding sotagliflozin, a dual sodium‐glucose co‐transporter (SGLT)1 and SGLT2 inhibitor, to optimized insulin therapy in adults with type 1 diabetes and baseline body mass index ≥ 27 kg/m2. Issue 3 (23rd December 2020) - Danne, Thomas; Edelman, Steven; Frias, Juan Pablo; Ampudia‐Blasco, Francisco Javier; Banks, Philip; Jiang, Wenjun; Davies, Michael J.; Sawhney, Sangeeta
Abstract: Sotagliflozin, a dual sodium‐glucose co‐transporter (SGLT)1/SGLT2 inhibitor, is currently approved in Europe as an adjunct to optimal insulin therapy in adults with type 1 diabetes (T1D) and a body mass index (BMI) ≥ 27 kg/m 2 . In this post hoc analysis, efficacy at 24 weeks and safety at 52 weeks from pooled phase 3 clinical trials were evaluated in patients with baseline BMI ≥ 27 kg/m 2 . Sotagliflozin 200 mg and 400 mg added to insulin reduced glycated haemoglobin level and increased time in range assessed by continuous glucose monitoring versus placebo and also reduced body weight and systolic blood pressure. Differences in efficacy endpoints between sotagliflozin and placebo tended to be greater among patients with BMI ≥ 27 kg/m 2 compared to those with baseline BMI < 27 kg/m 2 . Consistent with published results for the entire population, fewer severe hypoglycaemia and documented hypoglycaemia ≤3.1 mmol/L events and a higher incidence of diabetic ketoacidosis occurred with sotagliflozin versus placebo in patients with BMI ≥ 27 kg/m 2 . Sotagliflozin as an adjunct to optimized insulin therapy in overweight/obese patients with T1D addressed some unmet needs and may help achieve optimal glycaemic control, mitigating weight gain without increasing hypoglycaemia risk in this high‐risk population.